The art accompanying the Metamorphoses by Joža Lovrenčič - David Movrin (Keria: Studia Latina et Graeca)
The challenges of editing a translation, such as the one preserved in the manuscript with Ovid’s Metamorphoses by dr. Joža Lovrenčič, include deciding about the art that accompanies the text. One of the options are the copper engravings from the workshop of Johann Weichard Valvasor; however, they omit some of the central stories. A more complete series of 178 illustrations was created by Bernard Salomon. Among its many versions, the one published by the German woodcutter Virgil Solis stands out due to its quality. Lovrenčič himself came from the Slovenian Littoral and perhaps he would delight in the fact that the single copy in Slovenian libraries is preserved in Piran.